Bugis Philosophy of Life in Religious Harmony: George Simmel's Perspective - Alam Khaerul Hidayat; Masita (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This paper examines efforts to realize religious harmony in society by applying the Bugis philosophical concepts of